Study and Characterization of Polystyrene/Titanium Dioxide Nanocomposites (PS/TiO2 NCs) for Photocatalytic Degradation Application: a Review - Qabel Hamzah, Maytham; Oudah Mezan, Salim; Nihad Tuama, Alaa; Hasan Jabbar, Abdullah; Arif Agam, Mohd (International Journal of Engineering and Technology, 2018)
Synthetic polymer/TiO2 composite such as Polystyrene/TiO2 has become recent highly research materials due to its potential and significant application in various fields. we can tune the polymer and nanoparticles by different techniques such as change the materials concentration, Exposure of materials to laser radiation, Exposure of materials to laser radiation, especially in tuning the polystyrene/TiO2 composite energy band gap. In this review, several methods of preparation are briefly explored such as pan-milling, precipitation, melt compounding, dip-coating, solution cast, and sol-gel method. Some recent advancement that focuses on the two basic elements: polymer and TiO2 are also included especially discussing on photocatalytic degradation that introduces photon as manipulate parameter to tune the polymer/TiO2 composite energy band gap. Scanning electron microscope (SEM) analysis of various polymer/TiO2 (type n concentration) and Polystyrene/TiO2 (concentration and nanoparticles sizes) are the focus of the discussion before exposure to laser radiation as photodegradation source.Â Â Â